Urethane oligomers with pyrimidine rings - Ślączka, A.; Lubczak, J. (Polimery, 2022)
New urethane oligomers containing pyrimidine rings were obtained from N,N’-bis(hydroxymethyl)barbiturate and bifunctional isocyanates. The products were isolated and identified on the basis of elemental analysis, IR and 1H NMR spectroscopy. The oligomers obtained have higher thermal stability in comparison with their analogues obtained from aliphatic diols.